Investigation of using mangrove-inspired skirt pile group as a scour countermeasure. (15th December 2022) - Li, Xiwei; van Paassen, Leon; Tao, Junliang
Abstract: Mangrove forests are able to protect the coastline because their dense prop root system reduces the flow velocity and stabilizes sediments against erosion. Inspired by this unique character of the mangrove root structure, a ring of skirt piles is proposed as a measure to mitigate local scour around monopile foundations. Numerical simulations using computational fluid dynamics (CFD) modeling as well as laboratory flume experiments were conducted to evaluate the scour mitigation effect in clear water current. The simulation results reveal that the presence of skirt piles reduces the near-bed tangential velocity and affects the vertical flow field around the monopile. The experimental results indicate that if all other parameters are held constant, the scour depth and volume increase with skirt pile spacing, decreases with the number of skirt pile rings. With a single ring of skirt piles, the scour potential reaches the lowest with an intermediate critical submerged height of the skirt piles; the scour depth and volume increase when the submerged height deviates from the critical value. The comparison between the numerical and experimental results implies that the installation of the skirt piles has not only hydraulic but also geotechnical benefits for scour mitigation. Highlights: A scour countermeasure inspired by mangrove roots includes arrays of skirt piles. With skirt piles, the scour depth and volume around a monopile reduces by up to 65% and 90%, respectively. Skirt piles reduces flow velocity and bed shear stress around a monopile. It is hypothesized that downflow and installation-induced densification affect the scour patterns around the monopile.